Design and fabrication of a biodegradable face shield by using cleaner technologies for the protection of direct splash and airborne pathogens during the COVID-19 pandemic - Adib Bin Rashid; Nazmir-Nur Showva (Cleaner Engineering and Technology, 2023)
Due to global supply chain disruptions and high demand for personal protective equipment (PPE), the rapidly expanding COVID-19 crisis left millions of front-line fighters unprotected. The disposal of PPE in the environment caused significant environmental pollution. Hence, indigenous initiatives have been taken to fabricate antiviral and biodegradable face shields with the help of neoteric and cleaner technologies. This paper describes a novel endeavor to design, manufacture, and performance analysis of a face shield made by plastic injection molding and LASER Cutting. Because of the requirement of permanent wear, the face shield's ergonomic design is considered low weight and easy head fixation, alongside high production ability. Here, face shield frames are made with lightweight, biodegradable plastic called Poly Lactic Acid (PLA), whereas an optical grade PLA sheet is used as the visor for better clarity. Visors PLA Sheet is coated with Nano-Silver disinfectant spray to incorporate antiviral properties to the Faceshield. Partially circumferential adjustable elastic straps are used for comfortable head fixation. To evaluate the product, clinical fit tests along with statistical survey were conducted, and the feedback from the end-users on comfort (41% Excellent, 30% Good, 26% Average and 3% Poor), clear view (33% Excellent, 38% Good, 24% Average, and 5% Poor), design features (43% Excellent, 35% Good, and 22% Average), simplicity of installation and disassembly (29% Excellent, 33% Good, and 38% Average), and ease of wearing/removing (45% Excellent, 40% Good, and 15%Average) are encouraging.